Engineering Pagaralam-Indonesia Language Dictionary Software By Applying Voice Recognition - Robert Raical; Jemakmun; RM Nasrul Halim (Institute of Computer Science (IOCS), 2022)
Besemah/Pagaralam as one of the regions in Indonesia which is located in South Sumatra Province which has a regional language called Besemah Language. Besemah language is the language used by the indigenous people of Pagaralam or people outside Pagaralam to be able to interact. The search requires a system that is easy to do, for example through voice technology, so that users do not need to type in a search, namely voice recognition technology. Voice recognition technology is currently experiencing rapid development. Voice recognition or also known as speaker recognition is designed to recognize who is speaking. It uses the acoustic character of the sound which differs between individuals.